Foundations of flat patterning and draping : for the female form - McConnell, Larissa (Routledge, 2022)
"Foundations of Flat Patterning and Draping: For the Female Form provides the foundational tools necessary for success in the techniques of flat patterning and draping clothes and costumes. This book begins with the basics of taking measurements, preparing the fabric for draping, and preparing the dress form. The following chapters explore flat patterning and draping practices for bodices, skirts, pants, dresses, sleeves, collars, cuffs, and facings through detailed step-by-step instructions, checklists, and numerous diagrams. The bodice drafting instructions in this book, specifically, are a new method that accommodates all bust and cup sizes. There are instructions for small and large cup sizes allowing for a fit that does not gap at the armscye as typically happens with previous patterning methods, and additional sections for bodices and sleeves and how to manipulate them to create alternate looks. The techniques in this book generalize across sizes and shapes making it universally applicable for the student technician, as well as the person the garment is being developed for. Each method of drafting and draping has been class-tested and proven to produce well-fitting garments. Presented in an accessible format with clear instructions and detailed illustrations, this book is well suited for use as a textbook for the undergraduate college instructor teaching costuming or fashion, as well as for the student or individual learning on their own in theatre, film, or fashion industries"- Resumé vydavatel